Genetics of pulmonary hypertension and high-altitude pulmonary edema - Eichstaedt, Christina; Benjamin, Nicola; Grünig, Ekkehard (Journal of applied physiology, 2020)
Heritable pulmonary arterial hypertension (PAH) is an autosomal dominantly inherited disease caused by mutations in the bone morphogenetic protein receptor 2 (BMPR2) gene and/or genes of its signaling pathway in ~85% of patients. A genetic predisposition to high-altitude pulmonary edema (HAPE) has long been suspected because of familial HAPE cases, but very few possibly disease-causing mutations have been identified to date. This minireview provides an overview of genetic analyses investigating common polymorphisms in HAPE-susceptible patients and the directed identification of disease-causing mutations in PAH patients. Increased pulmonary artery pressure is highlighted as an overlapping clinical feature of the two diseases. Moreover, studies showing increased pulmonary artery pressures in HAPE-susceptible patients during exercise or hypoxia as well as in healthy BMPR2 mutation carriers are illustrated. Finally, high-altitude pulmonary hypertension is introduced and future research perspectives outlined.